2022
DOI: 10.21597/jist.1085847
|View full text |Cite
|
Sign up to set email alerts
|

Yenilebilir Doğal Bitkilerin Etnobotanik ve Gastronomik Açıdan Değerlendirilmesi: Edremit Körfezi (Balıkesir) Örneği

Abstract: Günümüzde insanların farklı kültürlere olan ilgisi, sağlıklı yaşam hakkında giderek bilinçlenmeleri, doğal gıdalara eğilim göstermeleri ve gastronomik deneyimler yaşama istekleri gibi farklı nedenler yöresel mutfaklara olan talebi giderek artırmaktadır. Ülkemizde, özellikle son yıllarda yapılan gastronomi yarışmaları ve ot festivalleri aynı zamanda yapıldığı bölgenin turizm çekim gücünü önemli derecede etkilemektedir. Balıkesir ilindeki Kaz Dağı, Madra Dağı, Ulus Dağı gibi zengin floristik alanlarda bolca yeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Çetinkaya and Yıldız (2018), found that the mallow plant was fried in oil and made with eggs, boiled and consumed by adding yoghurt, and made into a dish by adding herbs such as knotweed and evelik; Soup is made from fresh nettle leaves; Madimak plant is consumed both raw and cooked; Purslane plant is eaten both raw and cooked; They stated that both the core and the leaves of the radish plant are eaten. The above-ground parts of Chenopodium album, Stellaria media, Polygonum cognatum, and Urtica dioica plants; They stated that the leaves of Arum elongatum, Chondrilla juncea, Cichorium intybus, Capsella bursa-pastoris, Raphanus raphanistrum, Erodium cicutarium, Malva neglecta and Portulaca oleracea plants are consumed fresh or cooked (Aladı et al, 2022) . Although there were some differences in the parts of the plants used in this study, generally similar results were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Çetinkaya and Yıldız (2018), found that the mallow plant was fried in oil and made with eggs, boiled and consumed by adding yoghurt, and made into a dish by adding herbs such as knotweed and evelik; Soup is made from fresh nettle leaves; Madimak plant is consumed both raw and cooked; Purslane plant is eaten both raw and cooked; They stated that both the core and the leaves of the radish plant are eaten. The above-ground parts of Chenopodium album, Stellaria media, Polygonum cognatum, and Urtica dioica plants; They stated that the leaves of Arum elongatum, Chondrilla juncea, Cichorium intybus, Capsella bursa-pastoris, Raphanus raphanistrum, Erodium cicutarium, Malva neglecta and Portulaca oleracea plants are consumed fresh or cooked (Aladı et al, 2022) . Although there were some differences in the parts of the plants used in this study, generally similar results were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Arum species are calcium oxalate crystals, oxalic acid soluble oxalates, and plants with abundant volatile substances with strong local effects, and are known to cause an uncomfortable feeling similar to pins and needles in the mouth and tongue when consumed raw and fresh. In the study of Aladi et al (2022) stated that the leaves of these plants do not have a toxic effect when consumed after drying by the local people or when they are boiled and used in meals by removing the boiling water.…”
Section: Consumption Of Edible Seed Sproutsmentioning
confidence: 99%
“…The genus Raphanus L. is represented in the world by 4 species (5 taxa); It is represented by 2 species (5 taxa) in Turkey (The Plant List 2010; Güner et al 2012). One of the important species of the genus Raphanus is R. raphanistrum L. The roots and leaves of this species, known as Wild Radish (English) or Yabani turp (Turkish), are consumed in some countries, including Turkey, for food purposes (Baytop 1999;Aladı et al, 2022).…”
Section: Introductionmentioning
confidence: 99%